Translation and validation on household covid-19 food insecurity experience scale (covid-19 fies) and its association with psychological well being among low income women in Kelantan during the covid-19 pandemic - Haron, Muhammad Zulfahmi (2023)
Introduction: The COVID-19 pandemic is a public health and humanitarian crisis that threatens the food security and nutrition of millions of people around the globe. Worsening food insecurity level during pandemic may have long-term implications and lower the psychological well-being level of the vulnerable group particularly low-income women. Currently, there is no validated Malay instrument available to measure the food insecurity experience scale due to COVID-19 crisis and its association with psychological well-being in the country. Objectives Thus, the objective of first phase of this study was to translate the COVID-19 Food Insecurity Experience Scale (COVID-19 FIES) into Malay and to determine its construct validity and reliability. The second phase was to describe the proportion of individual and household food insecurity experience and its association with psychological well-being among low-income women in Kelantan during the COVID-19 pandemic. Methodology: Phase one involved ten and 68 mothers or women caretakers from Kota Bharu district were invited for face and construct validity, respectively. The second phase was a cross sectional study involving 252 mothers or women caretakers of malnourished children who were the recipients of Food Basket Program conducted at 24 health clinics in Kelantan from November 2022 to March 2023. All respondents were randomly selected by proportionate stratified sampling. The face validity has been tested by Face Validity Index (FVI) and the construct validity and reliability has been tested using exploratory factor analysis and Cronbach's alpha coefficient, respectively. The association between individual and household food insecurity experience with psychological well-being has been identified through Analysis of Covariance (ANCOVA) analysis. Results: The Item-Level Face Validity Index (I-FVI) range was 0.9 to 1.0 and the Scale-Level Face Validity Index (S-FVI) was 0.73. Three major components have been identified from exploratory analysis factors which are uncertainty component, quality component, and quantity component with factor loading range from 0.428 to 0.866 and acceptable reliability index (Cronbach's α = 0.710). A total of 26 (10.3%) households were identified as food security, 122 (48.4%) mild, 85 (33.8%) moderate and 19 (7.5%) severe food insecurity. There was no significant association between food security and food insecurity group for both individual and household experience level with mean psychological well-being score [-0.37 (-4.38, 5.11), p=0.880] among low-income women in Kelantan during COVID-19 even after controlling for possible sociodemographic confounders (ethnic, educational level and receiving supplementary food assistance) and covariates (age, number of children, number of household members and total household income). Conclusion: Malay version of COVID-19 Food Insecurity Experience Scale (COVID-19 FIES) is valid and a reliable tool to measure household food insecurity among low-income women in Kelantan. Although there was no significant association between food insecurity and psychological well-being, however, other study on structural relationship between sociodemographic with food insecurity as mediating effect, toward psychological well-being need to be carried out.